A Review on Hematuria in Children - Sarel Halachmi; David Kakiashvili; Shimon Meretyk (The Scientific World Journal)
Asymptomatic hematuria is very common in pediatric and adolescent patients. In contrast to painless hematuria in adults, the differential diagnosis and investigative modalities in the pediatric population is vastly different. This article presents the major diseases that may cause hematuria in children and suggests an evaluation algorithm for the pediatric urologist.